Pemanfaatan Alat Peraga Matematika Sebagai Jembatan Proses Abstraksi Siswa untuk Pemahaman Konsep - Elang Krisnadi (Prosiding Temu Ilmiah Nasional Guru, 2022)
One of the characteristics of mathematics is to have an object of study that is abstract andmakes the object difficult to observe and understand with the five senses. Meanwhile, the thinkingprocess of students in elementary school is still in the stage of concrete operation. To study abstractmathematical objects, an intermediary is needed as a way to reduce its abstraction, by using models ofconcrete objects. In mathematics learning, concrete object models are commonly referred to asmathematical teaching aids. The development of abstraction theories, either directly or indirectly, willnot be closely related to the process of learning mathematics in the classroom. In addition, learningmathematics that is fun, interesting, and simultaneously enhance meaningfulness at the elementaryschool level is becomes a hope of every student. Fun and meaningful learning can give students apositive attitude towards mathematics and can increase their understanding of mathematical concepts.In relation to this, the paper will discuss the abstraction process in mathematics learning integrated withthe use of teaching aids as an effort to provide alternative choices in overcoming various mathematicslearning problems. In the world of mathematics education, some abstract con